2019
DOI: 10.1002/mp.13948
|View full text |Cite
|
Sign up to set email alerts
|

An image regression motion prediction technique for MRI‐guided radiotherapy evaluated in single‐plane cine imaging

Abstract: Purpose To develop and evaluate a novel motion prediction method for magnetic resonance image (MRI)‐guided radiotherapy applications. This method, which we deem “image regression,” predicts future tissue motion based on a weighted combination of previously observed motion states. Motion predictions are derived from a sliding window of recent motion states which are defined by a temporal sequence of images. A key advantage of this method compared to other motion prediction methods is that its computational comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 33 publications
0
16
0
Order By: Relevance
“…Note that this process is currently 2D, due to a lack of commercially available real-time 3D imaging sequences. Recent studies however showed promising approaches towards realtime 3D MR image acquisition (53)(54)(55)(56) and reconstruction (57).…”
Section: Real-time Mrimentioning
confidence: 99%
“…Note that this process is currently 2D, due to a lack of commercially available real-time 3D imaging sequences. Recent studies however showed promising approaches towards realtime 3D MR image acquisition (53)(54)(55)(56) and reconstruction (57).…”
Section: Real-time Mrimentioning
confidence: 99%
“…The gating decision accuracy was defined as the proportion of predicted gating decisions that were correct compared to those derived directly from the images. The PPV was defined as the proportion of predicted beam‐on gating decisions that were correct 18 . Additionally, the effect of using a confidence estimator threshold on gating duty cycle was determined.…”
Section: Methodsmentioning
confidence: 99%
“…Motion predictions are obtained using an image regression motion prediction method previously developed by our group in the context of MRI-guided radiotherapy. 18,19 In this setting, each observation is a set of images. The prediction method identifies the K observations in a training set that are most similar to the current observation, derives weights that best estimate the current observation as linear combination of these training elements, and predicts motion by combining the future locations associated with the training elements with the same weights.…”
Section: A1 Proposed Confidence Estimatormentioning
confidence: 99%
See 1 more Smart Citation
“…For the problem of intraoperative target organ movement, many scholars and medical institutions have proposed various technical solutions, such as the passive pressure technique based on constrained organ motion space and the method of deep inspiration breath-hold [7,8], Gating technique based on the perception of organ motion cycle pattern [9] and movement prediction compensation algorithm [10], and methods such as four-dimensional CT and slow CT based on image scanning technology [11]. However, it is difficult to obtain the real movement of the intraoperative target area in real-time for all the above schemes.…”
Section: Introductionmentioning
confidence: 99%